THE EFFECT OF GUIDED DISCOVERY LEARNING OF STUDENT LEARNING LESSON MATERIALS ON IMPLEMENTING THE PROCEDURE OFMANUAL ELECTRIC WELDING IN LIGHT VEHICLE ENGINEERINGGRADE X SMK KARSA MULYA PALANGKA RAYA AT ACADEMIC YEAR 2015/2016 - Bayu C. Anggara; Vontas Alfenny Nahan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2016)
The purpose of this research is to know the effect of discovered guidance learning model to student’s learning achievement on the procedure implementation of manual welding subject in Class X of Light Vehicle Engineering Major (TKR) SMK Karsa Mulya Palangka Raya at academic year 2015/2016. This research is experimental type with using method of one group pre test-post test design where was held at SMK Karsa Mulya Palangka Raya. The sample took the Students of Grade X of Light Vehicle Engineering Major at around 28 persons. Research data is using quantitative data of test instrument of learning outcomes namely pre test score and post test value. Before applying it, the instrument is tested in grade X of Welding engineering major at SMKN 1 Palangka Raya. The result for 50 multiple choice questions has obtained the accepted 30 questions being the selected instrument in this paper. The outcomes of parameter hypothesis test utilizing t-test is that correlated 2 samples have been resulted the value of tcount > ttable (4,437 > 2,006). Due to tcount = 4,437 which is higher than ttable = 2,006, this means that Ho is unaccepted and H1 is accepted indicating that there is the influence of discovered guidance learning model to student’s learning achievement on the procedure implementation of manual welding subject in Class X of Light Vehicle Engineering Major (TKR) SMK Karsa Mulya Palangka Raya at academic year 2015/2016. All in all, this research concludes that the student’s outcome using that method was providing a progress comparing to previous condition.